2016
DOI: 10.1016/j.jnucmat.2016.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold rolling on the oxidation resistance of T91 steel in oxygen-saturated stagnant liquid lead-bismuth eutectic at 450 °C and 550 °C

Abstract: The compatibility of T91 steels having different preparation processes with oxygen-saturated stagnant lead-bismuth eutectic have been investigated at 450 o C and 550 o C. It is found that cold rolling decreases the thickness of the oxide scale of T91 steel by forming a continuous enhanced Cr-rich belt in the inner oxide layer next to the internal oxidation zone, which is attributed to the rapid diffusion of Cr induced by numerous non-equilibrium grain boundaries and migrating dislocations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In fact, except for the chemical composition, some methods that can accelerate the diffusion of Cr to form an effective Cr-rich oxide at the oxidation front also can improve the oxidation resistance of the alloy. We have reported that cold rolling enhances the oxidation resistance of T91 in LBE by introducing non-equilibrium grain boundaries and migrating dislocations into alloy, which accelerates the diffusion of Cr during the oxidation 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, except for the chemical composition, some methods that can accelerate the diffusion of Cr to form an effective Cr-rich oxide at the oxidation front also can improve the oxidation resistance of the alloy. We have reported that cold rolling enhances the oxidation resistance of T91 in LBE by introducing non-equilibrium grain boundaries and migrating dislocations into alloy, which accelerates the diffusion of Cr during the oxidation 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of the δ-ferrite phase is the largest in the 60%CR sample, followed by the 20%CR sample, and the as-cast sample is the smallest. It has been reported that the grain size of AFA steel gradually decreases with the increase in cold-rolling deformation [29], and grain refinement resulted from cold rolling could improve the high-temperature oxidation resistance of the steels [26,27].…”
Section: Microstructure Characteristics Observed From Cross-sectionmentioning
confidence: 99%
“…Yanar et al [24] compared the oxidation behavior of three AFA steels with different alloy compositions in dry air and water vapor environments (Air-10%H2O, Ar-3%H2O, and Ar-4%H2-3%H2O) and found that the oxidation resistance of the three AFA alloys is significantly reduced in an environment containing water vapor at 800 °C, and internal oxidation areas exist. Additionally, it is reported that grain refinement can help improve the high-temperature oxidation resistance of materials and the migration of dislocation promotes the diffusion of elements, allowing the protective oxidation film on the surface of the materials to be quickly formed [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Cold working also affects severely the oxidation behaviour of T91 and Si-enriched F/M steels [255,256]. Dong et al [255] reported that cold rolling decreased the oxide scale thickness on T91 F/M steels exposed to oxygen-saturated static liquid LBE at 450 • C and 550 • C for 2000 h. The authors attributed this phenomenon to the rapid diffusion of Cr to the steel surface and the subsequent formation of thinner, more protective chromia scales.…”
Section: The Role Of Steel Microstructure and Thermomechanical Statementioning
confidence: 99%
“…Cold working also affects severely the oxidation behaviour of T91 and Si-enriched F/M steels [255,256]. Dong et al [255] reported that cold rolling decreased the oxide scale thickness on T91 F/M steels exposed to oxygen-saturated static liquid LBE at 450 • C and 550 • C for 2000 h. The authors attributed this phenomenon to the rapid diffusion of Cr to the steel surface and the subsequent formation of thinner, more protective chromia scales. In that study, the numerous non-equilibrium GBs and migrating dislocations produced by cold rolling acted as fast diffusion paths for Cr, which also resulted in the formation of a continuous Cr-rich band next to the inner oxide scale adjacent to the IOZ.…”
Section: The Role Of Steel Microstructure and Thermomechanical Statementioning
confidence: 99%